1999
DOI: 10.1002/(sici)1096-9071(199907)58:3<296::aid-jmv17>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of the G serotype distribution of group A rotaviruses in Kenya from 1991 to 1994

Abstract: An epidemiological study on the G serotype distribution of group A rotaviruses (GARV) isolated in Kenya was carried out in one urban hospital in Nairobi and in two rural hospitals in Nanyuki and Kitui to clarify the prevalent G serotypes before future introduction of the ready licensed rotavirus vaccine in Kenya. A total of 1,431 stool specimens were collected from children, who were mainly outpatients, aged from 0 to 6 years old with acute gastroenteritis from August 1991 to July 1994. Samples positive for GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
4

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
3
39
4
Order By: Relevance
“…(G8P [4] and G2P [6] HRV strains were designated DS-1 like by RNA-RNA hybridization or electropherotype.) The G8 specificity (shown in yellow) is believed to be of bovine origin, and it has been suggested that G8 was introduced into HRV strains during several separate reassortment events (1,10,11,31,44,63). The P [6] specificity (shown in blue) is found in humans and pigs (38) and is present in more than a quarter of the HRV isolates found on the African continent (59).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…(G8P [4] and G2P [6] HRV strains were designated DS-1 like by RNA-RNA hybridization or electropherotype.) The G8 specificity (shown in yellow) is believed to be of bovine origin, and it has been suggested that G8 was introduced into HRV strains during several separate reassortment events (1,10,11,31,44,63). The P [6] specificity (shown in blue) is found in humans and pigs (38) and is present in more than a quarter of the HRV isolates found on the African continent (59).…”
Section: Figmentioning
confidence: 99%
“…The P [6] specificity (shown in blue) is found in humans and pigs (38) and is present in more than a quarter of the HRV isolates found on the African continent (59). DS-1-like HRV isolates with G8P [4] specificity have been found on several occasions on the African continent (12,13,18,44,46,63) and most likely acquired the G8 specificity through a reassortment event between a DS-1-like HRV and an RV with the G8 specificity (Fig. 4A).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The P genotypes are in brackets, whereas the P serotypes are open numbers. Epidemiological studies have shown that serotypes G1, G2, G3, and G4, associated with P1A (8) or P1B (4), have been the most common serotypes causing severe disease in children globally over the last 20 years (35,40). Genetic and antigenic variation has been recorded within the G1, G2, G3, and G4 serotypes (38).…”
mentioning
confidence: 99%
“…G I rotavirus has been the most predominant type in the world, while G4 rotavirus has been predominant in Kenya and some other countries occasionally (13,25). In this report we characterized G4 rotavirus in more detail.…”
mentioning
confidence: 99%